2011
DOI: 10.1159/000334479
|View full text |Cite
|
Sign up to set email alerts
|

Factors Associated with Fluoride Concentrations in Whole and Parotid Ductal Saliva

Abstract: Background/Aims: There are still uncertainties regarding the use of whole and parotid ductal saliva as indicators of chronic exposure to fluoride. This study evaluated the effect of water fluoride concentration, age, gender, geographical area and localization (urban/rural) on fluoride concentrations in whole and ductal saliva. Methods: Subjects (n = 300) aged 3–7, 14–20, 30–40 and 50–60 years, from five communities (A–E) with different fluoride concentrations in the drinking water, participated in the study. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 29 publications
0
3
0
Order By: Relevance
“…Our results showed that the F concentration of water (i.e., F area) was the most important factor influencing the 24-h UFE and F concentration in the other investigated biological markers (saliva, plasma, finger-and toenails). A study in 5 Brazilian communities with drinking water F concentrations of 0.09-1.68 mg/L also reported geographical area and water F concentration as the strongest influencers in whole and ductal saliva F concentrations, respectively [Fukushima et al, 2011], as well as in nail F concentrations [Fukushima et al, 2009]. When we examined the relationship between TDFI and various biomarkers, we found 24-h urine (Fig.…”
Section: Resultsmentioning
confidence: 63%
“…Our results showed that the F concentration of water (i.e., F area) was the most important factor influencing the 24-h UFE and F concentration in the other investigated biological markers (saliva, plasma, finger-and toenails). A study in 5 Brazilian communities with drinking water F concentrations of 0.09-1.68 mg/L also reported geographical area and water F concentration as the strongest influencers in whole and ductal saliva F concentrations, respectively [Fukushima et al, 2011], as well as in nail F concentrations [Fukushima et al, 2009]. When we examined the relationship between TDFI and various biomarkers, we found 24-h urine (Fig.…”
Section: Resultsmentioning
confidence: 63%
“…30 Besides, fluoride contents in saliva and urine in children are positively correlated with the fluoride levels in drinking water. 31 , 32 In this research, it was found that 39% of the drinking water samples presented fluoride levels above 1.5 mg/L. In addition to drinking water, other sources of fluoride have been described such as, fluoridated toothpastes, processed beverages and foods, salt, and other dental products.…”
Section: Discussionmentioning
confidence: 76%
“…Fluoride (F) has a fundamental role in maintaining the oral health, because of its potential to control the development of dental caries lesions (Fukushima et al, 2011). Dental caries is considered a chronic worldwide prevalent multifactorial disease, becoming a serious public health problem in developed countries, affecting 2.4 billion individuals, about 35.5% of the total population (Barrington et al, 2019), including around 60-90% of school-age children (Iheozor-Ejiofor et al, 2015).…”
Section: Introduction 1 Introductionmentioning
confidence: 99%